DUMPING DAN ANTI-DUMPING SEBAGAI BENTUK UNFAIR TRADE PRACTICE DALAM PERDAGANGAN INTERNASIONAL - Ella Apryani, Ni Wayan; Laksmi Danyathi, Ayu Putu (Kertha Negara : Journal Ilmu Hukum, 2014)
In a global free trade, states often aplly action that is generally called “dumping” as one of the strategies for dominating the market share that resulted in losses against other countries. As countermeasures, states practice antidumping policy that is derived from Article VI of GATT. However this makes not only the practice of dumping but also antidumping as an unfair competition (unfair trade practices) in international trade relations. This writing is aimed to describe the regulation of dumping and antidumping and also to analyze their status under Article VI of GATT.
Keywords: dumping, anti-dumping